Oxidation degree of graphene reflected by morphology-tailored ZnO growth. (October 2016) - Li, Changxia; Cheng, Zhihua; Gao, Jian; Han, Qing; Ye, Minghui; Zhang, Jing; Huang, Rudan; Qu, Liangti
Abstract: This work demonstrates the surface chemistry of graphene can be directly reflected by the visible zinc oxide (ZnO) nanostructures. When C/O atom ratio is smaller than 9, ZnO tends to self-assemble into hydrangea-like microstructure in the form of nanosheets on the graphene films and the size of ZnO microspheres decrease gradually with the increase of C/O ratio. In the case of C/O ratio of larger than 9, the sphere-shaped flowers disappear, followed by clavate structures. The larger C/O ratio is, the less the diameter of rods is. When C/O ratio is in the range of 8–9, there is a hybridized state composed of both of nanosheets and rods, where the rods are in the range of microns. The morphology evolution of ZnO is applied to graphene film with different oxidation degree modulated by HI acid or thermal treatment. What's more, hydrangea-like ZnO/graphene structure shows a good reversibility of the surface wettability irradiated with UV light and enhanced sensitivity to visible light irradiation, which will open up new opportunities for future optoelectronic devices.